THE MEDIATING ROLE OF VULNERABLE NARCISSISM LEVEL IN THE EFFECT OF LOCUS OF CONTROL ON ENTREPRENEURIAL POTENTIAL - Mert ÖZGÜNER (Fırat University, 2019)
Entrereneurship have a vital importance due to its a dynamics force for progress of economy especially seeing opportunities by environment, using these opportunities, due to provide employment that in the they create business, entrepreneurs provide positive contribution to national economy where they place. It’s not easy to set up a business and maintain it. Entrepreneurship is talent of finding selecting, interpretting opportunities and making innovation. It is very important that Entrepreneurs must have the courage, talent and creativity together. There are several factors that have decisive influence on entrepreneurship tendency or entrepreneurial intention. One of these factors is locus of control. Locus of control is a perception that there is a personal control in behaviour and action of persons, the consequences of actions should not be left to chance or to the outside World. Besides it is thought that based on relevant literatüre, vulnerable narcissistic meansthat extreme humbleness, sensitivity to critism, shyness, have an important role on the interaction of focus of control and entrepreneurship potantial. In this study, the mediating role of vulnerable narcissism level in the effect of locus of control on entrepreneurial potential the was tested by Hierarchical Regression Analysis. In this context, prepared hypotheses was tested on the 209 students who are studying at Besni Vocational School of Adıyaman University and have taken the Entrepreneurship Course in Academic Year 2016-2017. Research findings demostrate that the partial mediating role of vulnerable narcissism level in the effect of locus of control on entrepreneurial potential.